(untitled) (Journal of Business Management and Accounting, 2016)
CSR commitments should be viewed from a broad Islamic perspective of reducing poverty rate, and enhancing quality of Muslims’ lives. The purpose of this study was to determine how Bank Islam manages its stakeholders, and their issues, in designing CSR activities through the three level of maslahah. A group of CSR players at the bank has been interviewed together with on-field observations as well as documentation reviews to gain insights into the process of managing stakeholders. The findings indicated that the bank acknowledges the importance of managing stakeholders, and their issues, through the engagement of various CSR activities. In designing CSR activities, the process of identifying the stakeholders and their issues may need to be carefully examined to improve the impact of the activities on the recipients. This study offers a new insight to the body of knowledge of CSR from the Islamic perspectives of stakeholder management.